Why, when and how should hypertriglyceridemia be treated in the high-risk cardiovascular patient? - Watts, G; Karpe, F (2011)
Recent epidemiology attests that hypertriglyceridemia may be a causal risk factor for cardiovascular disease (CVD). The specific atherogenicity of hypertriglyceridemia relates to the accumulation in plasma of triglyceride-rich lipoprotein remnants. Hypertriglyceridemia also drives a 'global' atherogenic dyslipidemic profile, which is frequent in high-risk cardiovascular patients, such as Type 2 diabetics. Elevated triglyceride in fasting or nonfasting blood samples should be a trigger for assessing atherogenic components of the lipid profile, particularly HDL-cholesterol, non-HDL-cholesterol and apoB. Residual risk of CVD remains high in statin-treated diabetic patients owing to persistent atherogenic dyslipidemia, which is not fully corrected by these agents nor by the addition of ezetimibe. Hypertriglyceridemia may then be targeted with niacin, fibrates or n-3 fatty acids, after correcting aggravating factors, especially obesity and hyperglycemia. Fibrates consistently decrease coronary events in dyslipidemic patients in outcome studies. New evidence supports adding fenofibrate to a statin in Type 2 diabetics with residual hypertriglyceridemia and low HDL-cholesterol; extrapolating from a recent meta-analysis, a 15% reduction in triglycerides could translate into a further 15% reduction in coronary events. Ongoing clinical trials may provide new evidence for adding niacin to a statin. The value of higher doses of n-3 fatty acids in reducing CVD risk remains to be demonstrated. The high triglyceride/low HDL nexus is an under-recognized risk factor for CVD that merits more detailed clinical assessment and treatment, particularly in patients with Type 2 diabetes already receiving a statin.